MALT Lymphoma of the Bladder: A Case Report and Review of the Literature - Prashant Vempati; Miriam A. Knoll; Mahfood Alqatari; James Strauchen; Adriana K. Malone; Richard L. Bakst (Case Reports in Hematology)
The presentation of a MALT lymphoma in the bladder is exceedingly rare. Furthermore, the optimal treatment of primary MALT confined to the bladder remains to be defined. Here, we report a case of a 65-year-old female with primary MALT lymphoma treated with definitive radiation therapy. The patient received a total dose of 30 Gy in 20 equal daily fractions to the bladder and tolerated the treatment well. In addition, we have extensively reviewed the relevant literature to better define the optimal management of this rare disease. In conclusion, primary MALT lymphoma of the bladder represents a rare malignancy with excellent prognosis if detected at an early stage. For early stage disease, definitive radiation represents an excellent treatment modality with a minimal side-effect profile.